Push and pull motivations of Brazilian travel lovers - Gisele de Araujo Pereira; Marlusa Gosling (BBR: Brazilian Business Review)
Some people are more interested in traveling than others. What factors motivate people to travel? What are the factors that drive them to travel (push motives), and what are those that drive them to choose a certain type of trip (pull motives)? To answer these questions, this study conducted a twophase investigation with Brazilians citizens: an exploratory and qualitative phase with 16 in-depth interviews and a descriptive and quantitative phase based on a model supported by the 3M Model of Motivation and Personality (Mowen, 2000), and interpreted using structural equation modeling, with partial least squares (PLS). The most important motives identified were push motives (to search for self-knowledge and personal development) and pull motives (to face adventures and challenges, seek novelty, have stories to tell, and experience cultural diversity).